A filtering antenna with wide out‐of‐band suppression based on open‐stubs resonator. Issue 4 (29th December 2021) - Sun, Ji‐Qiu; Zhang, Li; Luo, Chuan‐Wei; Zhou, Shi‐Guo; Jiao, Yong‐Chang
Abstract: In this paper, a wide out‐of‐band suppression antenna with simple structure, low profile and filtering characteristics is presented. In order to improve the selectivity of the passband edge, two simple structures, namely U‐shaped slot and two slits, are introduced into the antenna to generate radiation nulls. To obtain a wide out‐of‐band suppression, the feeder with π‐shape stub is applied. The transmission nulls generated by the feeder are used to suppress stopband harmonics. In addition, a pair of parallel strips is introduced to enhance the gain suppression effect at the upper stopband. The measured results show that the average gain is 7 dBi, and the stopband suppression reaches 2.84 f 0 ( f 0 is the center frequency of the proposed antenna). The overall height of the presented antenna is 0.03 λ 0 ( λ 0 is the wavelength at the center frequency).